Seismic assessment of existing RC buildings before and after shear-wall retrofitting - Onat, Onur; Yon, Burak; Calayir, Yusuf (Croatian Soc Civil Engineers-Hsgi, 2018)
The existing reinforced concrete (RC) buildings are analysed in the paper before and after shear-wall retrofitting. For numerical application, an existing RC building was selected and retrofitted with shear walls. Incremental dynamic analyses and static pushover analysis of these buildings were performed using the distributed plastic hinge approach. The results show that seismic retrofitting with shear walls increases rigidity and capacity of the building, while decreasing lateral displacements and damage.
Keywords: structural analysis; damage; retrofitting; shear wall; reinforced concrete buildings